MODERNIZING MIDDLEWARE INFRASTRUCTURE: AN AMERICAN AIRLINES CASE STUDY - Anil kumar Thimmapuram, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the comprehensive middleware transformation initiative at American Airlines, demonstrating how modern architectural patterns and innovative technologies can revolutionize airline operations. The transformation encompassed multiple facets, including Kubernetes migration, real-time messaging architecture implementation, enhanced security protocols, and sophisticated monitoring solutions. Through strategic implementation of cloud-native technologies and microservices architecture, American Airlines significantly improved system reliability, operational efficiency, and security posture. The article highlights the critical role of organizational change management, security-first practices, and cross-functional collaboration in ensuring successful digital transformation. The initiative established new benchmarks for system performance and security in the aviation industry and laid a robust foundation for future technological advancement.